Produkt för att motverka mugg på häst - attfors, madeleine; gustafsson, Lisa; kettil, alexandra; ljungh, annie; thunholm, susanna; öhman, sara (My University, 2016)
Equine pastern dermatitis is a common problematic skin syndrome in horses. This project aims to find a simple, effective and consistent treatment method for the problem due to a great demand since there are no adequate treatment on the market today. This treatment method should consist of a product containing a mesoporous magnesium carbonate named Upsalite®, an antibacterial agent and a pressure specific bandage named Lundatex®. Through laboratory testing and creation of a business plan, a preliminary prototype has been developed for treatment of equine pastern dermatitis with a bacterial infection as perpetuating factor. Experimental results indicate a successful loading and secretion of an antibacterial agent in Upsalite®. Loaded Upsalite® furthermore implies bactericidal and moisture-adsorbent properties. The theoretical prototype developed from experimental results contains a version of Upsalite® with larger pores, alcogel as an antibacterial agent placed in a cotton pad. The business plan indicates a promising market for the product generated in the project. Customer segments that will be prioritized regarding marketing aspects are the segments of the equine business, the riding academy’s and the civil horse owners. Further studies needs to be done to verify and optimize the composition of the components in the generated prototype. Additional, clinical studies is necessary before commercialization of the product.
Keywords: Livsvetenskaper; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Husdjursvetenskap; Andra lantbruksrelaterade vetenskaper; Life Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Animal and Dairy Science; Other Agricultural Sciences